METODOLOGI PERUMUSAN AWAL BULAN KAMARIYAH DI INDONESIA - Amir, Rahma (UIN ALAUDDIN MAKASSAR, 2017)
This article discusses the importance of the determination of the beginning of the month on the calendar of islam in Indonesia, especially in the month because relating to worship or the major feast days of islam, thus the muslims should review the methods in determining the beginning of lunar month by the method of hisab and rukyat because there are some of the latest methods with the use of hisab and rukyat in the determination of the month in Indonesia. It can be said that the method is something absolute, while reckoning only support been seen on the basis of the calculation the first and as muslims argue that to determine the month to actually do the observation of the new moon directly.